A clinical, morphological and molecular study of 70 patients with gastrointestinal involvement in systemic mastocytosis - Lübke, Johannes; Naumann, Nicole; Hoffmann, Oliver; Horny, Hans-Peter; Sotlar, Karl; Rudelius, Martina; Metzgeroth, Georgia; Fabarius, Alice; Hofmann, Wolf-Karsten; Reiter, Andreas; Schwaab, Juliana (Scientific reports, 2024)
In 70 patients with KIT D816V positive systemic mastocytosis (SM) including 36 patients with advanced SM (AdvSM), we correlated the extent of reported mucosal mast cell ([m]MC) infiltration of the upper and/or lower gastrointestinal tract (UGIT, n = 63; LGIT, n = 64; both, n = 57) with symptoms and markers of MC burden/subtype. GI symptoms were reported by all patients (mean 2.1 number of symptoms). A strong mMC infiltration was identified in 24 patients (UGIT, 17/63, 27%; LGIT, 19/64, 30%). Concurrent involvement of UGIT and LGIT (n = 12) correlated with female gender (75%) and a higher symptom burden (mean 2.7) but not with MC burden or subtype. Significant differences between non-AdvSM and AdvSM were reported regarding food intolerance (54% vs. 17%), cramping (54% vs. 22%) and weight loss (0% vs. 64%). KIT D816V was identified in 54/56 (96%) available biopsies. In 46 patients, digital PCR revealed a correlation with low albumin levels (r =  − 0.270, P = 0.069) and the KIT D816V VAF in peripheral blood (r = 0.317, P = 0.036) but not with the extent of mMC infiltration or markers of MC burden/subtype. Although MC mediator triggered GI symptoms have a substantial impact on the quality of life, correlation to objective disease parameters is lacking thus making its systematic assessment challenging.
Gesehen am 19.07.2024